A study of business risks of public housing construction in Hong Kong and risk management methods adopted by contractors - Lee, Kin-wang (Curtin University, 2004)
The research conducted in this thesis studies the business risks considered as critical by construction contractors in the public housing construction industry in Hong Kong and the risk management methods adopted by these contractors. There is an inherent weakness in the public housing construction procurement in which price has been the overriding factor in the award of contracts and this has led to poor quality. A quantitative research method was adopted. The data for analysis included share price of listed construction contractors and other listed companies in Hong Kong. In addition, annual turnover of listed construction contractors from its company reports and available public housing projects to be tendered versus the number of prospective contractors were analysed. A main survey and a supplementary survey were also conducted after a qualitative initial study was launched to find out themes for the questions in the main survey. It is suggested that business risks of construction industry in Hong Kong are high when compared with non-construction business. As a consequence, risk premium from stocks of listed construction contractors should be higher than stocks of non- construction business. It is further suggested that risk premium of stocks of listed public housing construction contractors should be lower than other listed non- residential public buildings construction contractors due to adoption of subcontracting as risk management in the public housing construction industry. All these were being verified using share price, number of available public housing construction projects and company reports.The main survey was conducted to find out the perceptions of the public housing construction contractors on the business risks of its business due to: (a) its client, the Hong Kong Housing Authority, (b) statutory requirements, (c) penalty from poor performance and its ramifications, (d) suppliers and (e) staffing. The main survey also sought public housing construction contractors’ perception on the relative effectiveness of risk management proposals and quality improvement proposals. The supplementary survey looked at reasons for subcontracting in the Hong Kong construction industry. Exploratory factor analysis was carried out initially, which reduced the 47-item main survey questionnaire to 40 items with 8 factors and the 22-item supplementary survey to 20 items with 3 factors. In the main survey, for each of the factor identified, t-test of the mean on each of the item and of the summated items under each factor indicated the perceived business risks of public housing construction were: (a) critical due to "client" (the Hong Kong Housing Authority) - 7 critical items out of 9 items; (b) not critical due to "statutory requirements" -none of the 5 items is critical; (c) critical due to "poor performance ramifications" - all 2 items are critical; (d) critical due to "suppliers" - all 4 items are critical; (e) not critical due to "staff' -none of the 4 items is critical. For effectiveness of risk management measures to mitigate business risks due to suppliers and staffing, t-test of the mean was carried out. Risk management methods to mitigate business risks from: (a) "suppliers" were not perceived as effective - 1 effective item out of 3 items; (b) "staffing" were perceived as effective - 5 effective items out of 7 items. For effectiveness of quality improvement proposals, t-test of the mean indicated there were 3 effective items out of 6 items.Overall the quality improvement proposals were perceived as effective. For the supplementary survey to find out reasons for subcontracting in the Hong Kong construction industry, from the subcontractors' point of view, the business practice of main contractors was perceived as critical to the operation of subcontractors (all 7 items). On the other hand, relevant reason for further (secondary) subcontracting from subcontractors was due to lack of expertise (1 item out of 5 items). For quality improvement proposals, 6 items (workers registration, strengthen supervision by contractors on subcontractors, strengthen supervision by client, registry of subcontractor, award contract based on quality and treat subcontractor as business partners) were perceived as effective. Regression was carried out for the main survey and it was found that various statutory requirements were not significant predictors for the extent of pecuniary fines due to violations of statutory requirements. However site safety obligations were found to be a significant predictor to predict the period of suspension from tendering which would be considered as critically affecting the business of the contractor. For the supplementary survey, the regression was centred on relevant reasons for subcontracting (as independent variables) and extent of subcontracting (as dependent variable). The tests indicated that subcontracting to reduce risk of over expansion and price could be significant factors to predict the extent of subcontracting. To supplement what has been proposed as a possible solution (partnering) in improving the adversarial relationship amongst contracting parties in the construction industry, a case study was carried out to see how a local non-government organisation managed an underground transit system construction project by using "partnering".The case study indicated partnering could be useful to improve the inter-organisation co-operation in the construction industry. From the main survey, supplementary survey and the subsequent analysis as well as the case study, the most significant implication of this research is the need to have equitable terms in the contract between clients and its construction contractors. In the competitive public housing construction industry in Hong Kong, award of contract by price alone to the lowest bidder would not induce quality performance from construction contractors. To cater for fluctuating workload and risk of over- expansion, subcontracting is a form of risk management practiced by construction contractors. Subcontracting cannot be stamped out and to induce quality performance from construction contractors and subcontractors, what is essential between clients and construction contractors (equitable terms) is equally applicable between construction contractors and its subcontractors.